Manejo Forestal Comunitario: ¿una solución socialmente innovadora para abordar la conservación de los bosques? El caso de la Comunidad Nativa Callería (Ucayali, Perú) - Calero Valdez, Diego (2022)
Given the increasing speed of deforestation in the Amazonia and the problems faced by local communities and indigenous people who depend on forestry resources, the need for sustainable and collaborative forest management is evident. This essay evaluates the extent to which community-based conservation strategies could be framed into the social innovation approach, based on the experience of Community Forest Management in Callería Native Community (Ucayali, Peru). To address this purpose, different academic sources on Community Forest Management experiences within and outside the Amazon region and the case study itself were consulted, as well as other sources referring to the concepts of conservation, socio-ecological systems, governance of the commons and social innovation. The conclusion of this essay is that Community Forest Management could be largely framed as a solution within a social innovation approach, because it has enabled the Callería Native Community to achieve the three dimensions of social innovation: meet their human needs, develop new relationships and organizational structures, and increase their socio-political capacity. However, not all community conservation strategies are the same, as they are context specific.